2011
DOI: 10.1128/mcb.06297-11
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Single Downstream Target BAG1 Activates the Latent Apoptotic Potential of MYC

Abstract: Aberrant MYC expression is a common oncogenic event in human cancer. Paradoxically, MYC can either drive cell cycle progression or induce apoptosis. The latent ability of MYC to induce apoptosis has been termed "intrinsic tumor suppressor activity," and reactivating this apoptotic function in tumors is widely considered a valuable therapeutic goal. As a transcription factor, MYC controls the expression of many downstream targets, and for the majority of these, it remains unclear whether or not they play direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Interestingly, both MAD2L1 and BAG1 have been shown to be induced by MYC (27,28), and we confirmed that both genes were up-regulated in MCF10A-MYC cells. Consistent with the results obtained in B cells, induction of miR-28 led to a reduction of MAD2L1 and BAG1 (Fig.…”
Section: Mad2l1 Mediates Mir-28-induced Reduction Of Proliferationsupporting
confidence: 79%
See 2 more Smart Citations
“…Interestingly, both MAD2L1 and BAG1 have been shown to be induced by MYC (27,28), and we confirmed that both genes were up-regulated in MCF10A-MYC cells. Consistent with the results obtained in B cells, induction of miR-28 led to a reduction of MAD2L1 and BAG1 (Fig.…”
Section: Mad2l1 Mediates Mir-28-induced Reduction Of Proliferationsupporting
confidence: 79%
“…Deregulation of ERK signaling is found in many different cancers, including B-NHL, and its inhibition is also associated with an increase in apoptosis (31,32), including MYC-induced apoptosis (28). Thus, elevated BAG1 levels can protect the cells from apoptosis and, by activating ERK1/2, may favor survival and proliferation in lymphomas lacking miR-28 expression.…”
Section: Mir-28 As a Candidate Tumor Suppressor In Gc-derived Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal tumor models, loss of even a single copy of the BAG-1 gene decreases tumor formation (Gotz et al 2004), presumably owing to heightened apoptosis of the nascent tumor cells. Our analysis showed that induction of BAG-1 by MYC is a critical event in dampening the latent apoptotic effects that MYC overexpression otherwise exerts (Zhang et al 2011). Although BAG-1 is expressed as multiple protein isoforms with potentially distinct functions and has many client proteins beyond BCL-2 (Wang et al 1996;Luders et al 2000;Cato and Mink 2001;Lin et al 2001;Arhel et al 2003), these studies provide further evidence that modulating the prosurvival/proapoptotic balance in the BCL pathway is an important means by which MYC controls its biological effects.…”
Section: Other Bcl Family Events That Participate In Regulating Myc-dmentioning
confidence: 62%
“…An additional link between regulation of the BCL-2 pathway and MYC's apoptotic effects was shown in recent studies from our group that identified the BAG-1 gene product as a critical, direct downstream target of MYC (Zhang et al 2011). BAG-1 was first isolated as a BCL-2 chaperone that has potent prosurvival effects (Takayama et al 1995).…”
Section: Other Bcl Family Events That Participate In Regulating Myc-dmentioning
confidence: 87%